Ethical concerns for maternal surrogacy and reproductive tourism - Deonandan, Raywat; Green, S; Van Beinum, A (Université d'Ottawa | University of Ottawa, 2012)
Reproductive medical tourism is by some accounts a multibillion dollar industry globally. The seeking by clients in high income nations of surrogate mothers in low income nations, particularly India, presents a set of largely unexamined ethical challenges. In this paper, eight such challenges are elucidated to spur discussion and eventual policy development towards protecting the rights and health of vulnerable women of the Global South.